Effective implementation of continuing professional development for South African teachers - Steyn, Trudie (Acta Academica: Critical views on society, culture and politics, 2009)
The article attempts to satisfy two objectives: to arrive at a clear understanding of effective professional development (PD) programmes for teachers, and to outline how key aspects could influence the effective implementation of the National Policy Framework for Teacher Education and Development in South Africa, in particular that of CPTD. The article focuses on the following aspects: teachers’ learning, teachers’ commitment, quality leadership, the school context and requirements for PD programmes.